2018
DOI: 10.5694/mja17.00872
|View full text |Cite
|
Sign up to set email alerts
|

Sports injuries in Victoria, 2012–13 to 2014–15: evidence from emergency department records

Abstract: Assessing sports injury rates corrected for participation rates and evaluating the relative severity of injuries is important for monitoring safety. Our findings can assist decisions about which sports should be the focus of injury prevention efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 8 publications
0
23
1
Order By: Relevance
“…Namely, an Australian study reported an increase in sports injury-related ED visits between 2012 and 2015. 21 Furthermore, an American study on sports-related ED visits among individuals aged 5-18 years reported an increase in sports-related injuries between 2009 and 2013, 6 whereas we found a decrease among individuals aged 0-17 years between 2009 and 2018. This difference could be explained by the fact that in the current study only severe sports-related ED visits are included.…”
Section: Comparison With Other Studiescontrasting
confidence: 50%
“…Namely, an Australian study reported an increase in sports injury-related ED visits between 2012 and 2015. 21 Furthermore, an American study on sports-related ED visits among individuals aged 5-18 years reported an increase in sports-related injuries between 2009 and 2013, 6 whereas we found a decrease among individuals aged 0-17 years between 2009 and 2018. This difference could be explained by the fact that in the current study only severe sports-related ED visits are included.…”
Section: Comparison With Other Studiescontrasting
confidence: 50%
“…The article by Fernando and colleagues 4 reinforces the potential value of this approach, providing clear information about the most frequent sport‐related injuries, as well as preliminary estimates of per participant rates of injury. Ideally, health organisations should work with the national governing bodies of sports to achieve consensus on injury reporting and the impact of prevention strategies.…”
mentioning
confidence: 84%
“…Brukner and colleagues 3 searched for media reports of fatalities caused by head injuries in cricket over the past 160 years. Fernando and her co‐authors 4 report an excellent audit of the health care costs to society associated with sport‐related emergency department attendances in Victoria, coupled with an analysis of the relative risk and health costs of specific activities, while Prabhakaran and colleagues 5 provide a snapshot of some of the dangers for the participants of junior motocross. Franklin and his co‐authors 6 emphasise the need for education to reduce the number of preventable deaths from an under‐appreciated form of drowning.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 The injury presentations by Australian football players to emergency departments are both the highest and the most costly of any team sport in Australia. 14,15 Hospital presentations, however, may not represent the true incidence of injuries in Australian football because less severe injuries may present to independent health professionals rather than hospitals. Some injuries may not even receive medical attention depending on the resources or personnel available.…”
mentioning
confidence: 99%